2022
DOI: 10.1002/cbic.202200091
|View full text |Cite
|
Sign up to set email alerts
|

High Versatility of IPP and DMAPP Methyltransferases Enables Synthesis of C6, C7and C8Terpenoid Building Blocks

Abstract: The natural substance class of terpenoids covers an extremely wide range of different structures, although their building block repertoire is limited to the C5 compounds DMAPP and IPP. This study aims at the characterization of methyltransferases (MTases) that modify these terpene precursors and the demonstration of their suitability for biotechnological purposes. All seven enzymes tested accepted IPP as substrate and altogether five C6 compounds and six C7 compounds were formed within the reactions. A high se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…HumMT can react with SAM and IPP in vitro to produce the C6 compound 5-methyl-isoprenol. Additionally, it reacts with DMAPP to undergo a methylation modification at the C2 position, thereby producing a dephosphorylated product of 2-methyl-IPP, 2-methyl-isoprenol (Drummond et al 2022 ). Furthermore, a gene, lon23, identified from S. argenteolus sharing 38% homology in amino acid sequence with GPPMT identified from S. coelicolor , could catalyze the formation of 3 Z -3-methyl IPP ( Z -homo-IPP) in the presence of Mg 2+ and SAM using IPP as a substrate (Ozaki et al 2018 ).…”
Section: Microbial Biosynthesis Of Noncanonical Terpenoidsmentioning
confidence: 99%
“…HumMT can react with SAM and IPP in vitro to produce the C6 compound 5-methyl-isoprenol. Additionally, it reacts with DMAPP to undergo a methylation modification at the C2 position, thereby producing a dephosphorylated product of 2-methyl-IPP, 2-methyl-isoprenol (Drummond et al 2022 ). Furthermore, a gene, lon23, identified from S. argenteolus sharing 38% homology in amino acid sequence with GPPMT identified from S. coelicolor , could catalyze the formation of 3 Z -3-methyl IPP ( Z -homo-IPP) in the presence of Mg 2+ and SAM using IPP as a substrate (Ozaki et al 2018 ).…”
Section: Microbial Biosynthesis Of Noncanonical Terpenoidsmentioning
confidence: 99%
“…Recently, additional routes have been discovered for the production of noncanonical terpenoids, whose biosynthesis requires C -methyltransferases from bacteria. IPP/DMAPP methyltransferases have been shown to convert C 5 prenyl substrates to irregular C 6 ( 91 – 95 ), C 7 ( 96 – 100 ), and C 8 diphosphates ( 101 ), which could serve as building blocks for the generation of new terpenoids [ 51 ] ( Figure 7 ). Furthermore, a series of noncanonical C 11 , C 12 , C 16 , and C 17 prenyl substrates were synthesized in Escherichia coli harboring heterologously expressed IPP methyltransferase (IPPMT) from Streptomyces monomycini .…”
Section: Reviewmentioning
confidence: 99%
“…Nevertheless, recently it has been shown that bacteria can produce structurally highly diverse triterpenes also from regularly-connected pyrophosphate precursors by specialized enzymes along the Type I pathway. [3] These [6]-terpenes are structurally very different compared to common triterpenes of the [3 + 3]-terpene type that are precursors of steroids. Longer regular terpenes are usually pyrophosphates used in the biosynthesis of ubiquinone in eukaryotes [4] or menaquinone in bacteria.…”
Section: Introductionmentioning
confidence: 99%